استراتيجيات تسوية المنازعات الإدارية - Saleh, Jumah Qadir (Journal of Legal and Political Studies, 2025)
Administrative disputes are among the most important issues that significantly impact the effectiveness of government performance and the stability of relations between the administration and individuals. Traditional methods of resolving these disputes, such as direct recourse to the courts, often result in prolonging the conflict and wasting time, effort, and financial resources. It is advisable to adopt alternative strategies that contribute to achieving swift justice and providing appropriate solutions. This research addresses a range of arguments surrounding administrative disputes, focusing on their definition and identifying their types, such as disputes related to individual rights or administrative decisions. The research also explores the unique characteristics of these disputes, such as the unequal legal standing of the parties, as the administration enjoys special privileges that necessitate providing legal protection for individuals. The importance of administrative courts is highlighted in protecting rights from administrative abuse, as they represent an effective means of challenging administrative decisions. Alternative dispute resolution strategies extend to include mediation, arbitration, and conciliation. Mediation is an effective method for finding amicable solutions that strengthen relations between disputing parties. This process is characterized by its flexibility and confidentiality, which helps alleviate the burden on the judiciary. On the other hand, arbitration provides a legally binding mechanism that guarantees a fair ruling, while conciliation is a preliminary step aimed at bridging the gap between the parties' viewpoints. The research also points to the concept of "dismissal of litigation," which enables parties to resolve administrative disputes without prejudice to their rights. The research highlights the importance of establishing a culture of amicable solutions within government entities to strengthen their relationships with citizens. Ultimately, the research recommends promoting the use of alternative strategies and developing legal awareness among individuals and government entities, which will contribute to reducing conflicts, increasing the efficiency of the administrative system, and ensuring greater stability in relations between the administration and citizens. Keywords: Administrative disputes, alternative strategies, negotiation, mediation, arbitration
Keywords: Keywords Administrative disputes; alternative strategies; negotiation; mediation; arbitration